Glacierized headwater streams as aquifer recharge corridors, subarctic Alaska - A. K. Liljedahl; A. Gädeke; S. O'Neel; T. A. Gatesman; T. A. Douglas (Geophysical Research Letters)
Abstract Arctic river discharge has increased in recent decades although sources and mechanisms remain debated. Abundant literature documents permafrost thaw and mountain glacier shrinkage over the past decades. Here we link glacier runoff to aquifer recharge via a losing headwater stream in subarctic Interior Alaska. Field measurements in Jarvis Creek (634 km2), a subbasin of the Tanana and Yukon Rivers, show glacier meltwater runoff as a large component (15–28%) of total annual streamflow despite low glacier cover (3%). About half of annual headwater streamflow is lost to the aquifer (38 to 56%). The estimated long‐term change in glacier‐derived aquifer recharge exceeds the observed increase in Tanana River base flow. Our findings suggest a linkage between glacier wastage, aquifer recharge along the headwater stream corridor, and lowland winter discharge. Accordingly, glacierized headwater streambeds may serve as major aquifer recharge zones in semiarid climates and therefore contributing to year‐round base flow of lowland rivers.